Synthesis, characterization, electrochemical and spectroelectrochemical properties of peripherally tetra-substituted metal-free and metallophthalocyanines - KOCA, ATIF (ELSEVIER SCI LTD, 2013)
In this study, the synthesis, electrochemical and spectroelectrochemical properties of peripherally 2-(2,2,4,7-tetramethyl-3,4-dihydroquinolin-1(2H)-yl)ethanol substituted novel metal-free 4, Zn(II) 5, Ni(II) 6, Co(II) 7 and Cu(II) 8 phthalocyanine derivatives are reported. These new compounds have been characterized by using UV-Vis, IR, H-1 NMR, C-13-NMR (just for phthalonitrile derivative) and MS spectroscopic data. Electrochemical and spectroelectrochemical measurements exhibit that while CoPc gives a metal-based reduction process in addition to the ring-based reduction process, all the other complexes give common ring reduction reaction of MPcs which have redox inactive metal center. 2-(2,2,4,7-tetramethyl-3,4-dihydroquinolin-1(2H)-yl)ethanol groups which substituted on the periphery of the complexes provides electropolymerization of the complexes during the anodic potential scans. Type of the metal center of the complexes, which was used potential windows and the cycle numbers affect the character of the polymerization processes during the cyclic voltammetry measurements. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Metallophthalocyanine; Synthesis; Microwave; Electrochemistry; Spectroelectrochemistry; Electropolymerization; SITU ELECTROCOLORIMETRIC CHARACTERIZATION; ELECTROCHROMIC MATERIALS; COBALT PHTHALOCYANINE; ZINC PHTHALOCYANINES; CATALYTIC-ACTIVITY; OXIDATION; MOIETIES; CO(II)